Toward an Eco-Industrial Park Framework in Punjab : Regulatory and Institutional Strengthening for Industrial Estates - World Bank (World Bank, Washington, DC, 2021)
The aim of this report is to provide the Government of Punjab with a preliminary overview of opportunities and obstacles for the adoption of the EIP Framework by industrial estates (IEs) in Punjab, based on the World Bank Group's experience with emerging economies in implementation of the EIP Framework, as well as the results from research on policy regimes and industrial practices in Punjab. As part of this analysis, Sundar Industrial Estate (SIE) has been selected to pilot the high-level technical analysis on the environmental, social, and economic areas to improve, to operationalize the EIP Framework. Results and recommendations in this report are delivered as part of the broader support of the World Bank Group to the government through the Punjab Green Development Program (P165388). In a 2014 assessment of environmental management for Pakistan's industrial growth, the main findings and recommendations suggest that "to strengthen Pakistan’s industrial growth and industrial estates, the government must provide: (i) sectoral policies that support the greening of Pakistan's industrial sector to enhance international competitiveness; (ii) upgraded trade facilitation and sustainable infrastructure (particularly transport and energy infrastructure) to address some of the spatial aspects of industrialization; and (iii) strong institutions for effective industrialization initiatives, including those for small and medium enterprises." As IEs can play a pivotal role in industrial development, it is expected that the EIP Framework will help achieve the vision of Punjab's Growth Strategy 2023 to create "a globally connected and competitive, equitable, culturally vibrant and technologically advanced Punjab with sustainable economic growth driven through a dynamic private sector, an efficient public sector, rich and productive human capital and, a regionally equalized development footprint by 2023."